ANDEAN COMMUNITY MEMBERS IN THE CHILEAN GOVERNMENT (ARICA, 1880 - 1929) - Díaz Araya, Alberto (Revista de Historia Social y de las Mentalidades, 2011)
Assesses the impact generated in the rural Andes Arica for implementing the administrative structure and bureaucracy in Chile af ter the Pacific War. Through documentary record makes explicit the participation of indigenous community members in the plot Chilean state over a period of political and national identities.